Organisasi Sosial Keagamaan Nahdlatul Ulama: Tokoh dan Kegiatannya dalam Bidang Pendidikan Islam - Ramli, Ramli; Rama, Bahaking; Syamsuddin, Syamsuddin (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2024)
This article aims to find out the role of the religious organization Nahdlatul Ulama and its figures in the field of Islamic education. This research is carried out through a qualitative approach with a literature study approach. The preparation of the article is carried out by examining various sources that are directly related to the focus of this research. The main sources of research data are reference books and research articles published in various scientific journals and indexed by google scholar. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The findings of the analysis are that Islamic education has an influence on socio-culture, in the sense of providing philosophical insights, direction of views, behavioral motivations, and guidelines for change until the formation of a new social reality. The renewal of NU education is a mirror of the modernity of Islamic boarding school educators who are trying to bring their citizens to a new perspective in the field of education, as a means of maximizing Islamic teaching educational activities in the modern period. Reform in learning among the community, both formal schools and Islamic boarding schools, has progressed in learning methods not only using the memorization method in learning but also including lecture methods, discussion methods, Tahzib wa Targib methods (advising and reprimanding), question-answer methods, so that learning methods for students or students no longer use the memorization method alone, but combine the methods according to what is learned